Penerapan Knowledge Sharing Pada Sektor Publik: Perspektif Bibliometrik - Retno Andini; Tamara Adriani Salim (Media Pustakawan, 2024)
This study aims to investigate the research dynamics related to the Application of Knowledge Sharing in the Public Sector. The study was conducted in December 2023 by searching the Scopus database with the keywords "knowledge sharing" and "public sector". The search results were analyzed and processed using the VOSViewer application program to identify the bibliometric map of the development of research in the field of knowledge sharing in the public sector. The results show that the number of research publications in the field of knowledge sharing in the public sector on Scopus from 2019 to 2023 has experienced a significant increase and has been most published in the VINE Journal of Information and Knowledge Management Systems. Knowledge Sharing research in the Indonesian public sector is considered less popular. The most productive researcher in publishing research results is Sreejith Balasubramanian, affiliated with Middlesex University Dubai. Through network visualization, it shows that the research development map regarding knowledge sharing in the public sector is divided into 6 clusters. Cluster 1 consists of 15 topics, cluster 2 consists of 14 topics, cluster 3 consists of 12 topics, cluster 4 consists of 12 topics, cluster 5 consists of 10 topics, and cluster 6 consists of 5 topics. Research related to this topic in Indonesia is still focused on business, management, and accounting subjects in several institutions, with collaboration between researchers that needs to be improved.